Unfolding the Concept of Flexibility in Collaborative Housing Design - Rolando, Ludovica (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
The article discusses the concept of flexibility in architecture and its application in collaborative housing projects. It explores three key connotations of flexibility - redundancy, technical means, and political strategy - as put forth by Adrian Forty. The design strategies for flexibility in collaborative housing include filter elements to create an intimacy gradient, redundant circulation spaces, programmatic genericness of spaces, and a wide variety of typologies and technical devices. The article also discusses the role of collective decision-making in collaborative housing design and the construction of a shared meaning system to guide future choices.
Keywords: Flexibility; Housing Revolution; Collaborative Housing; Cohousing